Survey of Physicians to Assess the Initial Level of Knowledge as a Mechanism for Increasing the Efficiency of Educational Programs in the Field of Rational Antimicrobial Therapy - O. G. Ni; I. N. Ochakovskaya; N. E. Shabanova; G. A. Penzhoyan; G. Yu. Model; S. V. Yakovlev (Антибиотики и Химиотерапия)
One of the reasons of the failure of educational activities in the field of rational antimicrobial therapy is, most likely, the discrepancy between the level of initial training of students and the complexity of the presented material. The aim of this study was to assess the baseline knowledge of physicians in the field of microbiology, clinical pharmacology of antimicrobial agents and the level of antibiotic resistance in health facilities to develop an effective training program. Materials and methods. The study was conducted in the framework of implementation of the first phase of the antimicrobial stewardship program - SCAT program (Strategy for the Control of Antimicrobial Therapy). An anonymous survey of physicians of different specialties was carried out. Clinical pharmacologists composed the questionnaire, which included questions of different levels of complexity, divided into thematic blocks. The results of the survey were evaluated and compared depending on specialty and experience. The expected and real level of knowledge was analyzed. Results. 110 doctors of different specialties have participated in the survey. The respondents showed a low level of knowledge in the scope of the inquiry (50% correct answers on average), survey results significantly depended on specialty. The correlation between results and experience was also revealed - the knowledge was accumulated in the first 15 years of experience, while the number of correct answers among specialists with more extensive professional experience had a tendency to decrease. The complexity of the questions predicted by the experts did not correspond with the actual one in 66% of the cases. In 96% of inconsistencies, the real complexity was higher than the predicted one. Conclusion. The results of the study revealed that experts should assess the baseline level of knowledge of specialists more objectively. The training course should be as understandable and interesting for the audience as possible. It may also be advisable to develop various training programs for doctors of different specialties. The main emphasis should be placed on the training of young doctors, unobtrusively involving doctors with greater clinical experience in the process, if possible. The small group of respondents and only one center that participated in the survey do not allow making generalizing conclusions.